An assessment of agricultural freight transportation in Saki area of Oyo state, Nigeria - Fasina, Simeon Oluwagbenga (Logistics and sustainable transport, 2020)
Transportation no doubt remains a catalyst for all aspect of socio-economic and environmental development. Without its singular significance of mobility and accessibility for farmers, agricultural produce will rot on farms, while efforts in providing food would be fruitless. This paper assessed agricultural freight transportation in Saki area of Oyo State with a view of enhancing better product delivery mechanisms for farmers. It examined farmers’ socio-demographic; nature of farming and farm characteristics; and appraised the relationship between attributes of agricultural production and freight movement. Primary data employed consists of a questionnaire designed for farmers, structured interview for government officials complemented with personal field observations of agricultural freight transportation. 225 farmers were randomly selected for questionnaire administration. Major findings revealed that food crops, vegetables, fruits and poultry products are in persistent motion in the study area and that agricultural freight is a neglected sector with significant consequences on the access to cheap and affordable urban wellbeing. Findings also revealed that agricultural freight transportation within the study is very poor and uneconomical, as this depletes farmers’ profit-making. Regression analysis results show a significant relationship between attributes of agricultural freight and transport cost (F19205 11.916= P<0.05). The study recommends extensive road rehabilitation and constructions within the study area; provision of technological driven distribution and storage infrastructural facilities; creation of a databank for agricultural freight transport; reorganization and empowerment of farmers and improvement of rural infrastructure in Oyo state and Nigeria as a whole.
Keywords: agricultural freight; farmers; kmetijski tovorni promet; kmetje; območje Saki; Saki area; transport; transportation